2010
DOI: 10.1111/j.1365-2966.2009.15635.x
|View full text |Cite
|
Sign up to set email alerts
|

3D spectroscopy of merger Seyfert galaxy Mrk 334: nuclear starburst, superwind and the circumnuclear cavern

Abstract: We are presenting new results on kinematics and structure of the Mrk 334 Seyfert galaxy. Panoramic (3D) spectroscopy is performed at the 6-m telescope of the Special Astrophysical Observatory of the Russian Academy of Sciences using the integral-field Multi-Pupil Fiber Spectrograph (MPFS) and scanning Fabry-Pérot interferometer. The deep images have revealed that Mrk 334 is observed during the final stage of its merging with a massive companion. A possible mass ratio ranges from 1/5 to 1/3. The merger has trig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…The shells are the debris of this satellite and they mark the satellite's movement around Mrk 334. Brightness estimation for the tidal filaments yields a mass ratio of 1/5 to 1/3 for the interacting galaxies, which is close to the adopted boundary between minor and major merging (Smirnova & Moiseev 2010). According to HST observations (Deo, Grenshaw & Kraemer 2006), the nuclear dust morphology is chaotic, extensive star formation is taking place and the nuclear region shows two bright nuclei.…”
Section: Bta Data Versus Sdss Images: Individual Objectssupporting
confidence: 77%
See 1 more Smart Citation
“…The shells are the debris of this satellite and they mark the satellite's movement around Mrk 334. Brightness estimation for the tidal filaments yields a mass ratio of 1/5 to 1/3 for the interacting galaxies, which is close to the adopted boundary between minor and major merging (Smirnova & Moiseev 2010). According to HST observations (Deo, Grenshaw & Kraemer 2006), the nuclear dust morphology is chaotic, extensive star formation is taking place and the nuclear region shows two bright nuclei.…”
Section: Bta Data Versus Sdss Images: Individual Objectssupporting
confidence: 77%
“…These observations aimed at a detailed investigation of the gas ionization properties as well as stellar and gas kinematics in the target galaxies, in order to find a possible mechanism of AGN fuelling related to jet/cloud interaction etc. The results for several individual galaxies were published (see, for instance, Ciroi 2001; Ciroi et al 2005; Radovich et al 2005; Smirnova, Moiseev & Afanasiev 2006; Smirnova & Moiseev 2010). In order to improve our knowledge about targets for which 3D spectroscopic data were available, a deep imaging observation programme was started.…”
Section: Sample Selection and Observationsmentioning
confidence: 99%
“…0.95, −0.18 and −0.55 dex, respectively) to study the possible presence of AGN activity. UCM 0000 has been previously classified as an Sy1.8 galaxy by Véron‐Cetty & Véron (2006) and recently studied by Smirnova & Moiseev (2010). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting the characteristic radius of the galaxy R 25 ≈ 50 arcsec estimated from the fig. 4 in Smirnova & Moiseev (2010), the relative distance of the outer loop and arc is inferred to be ∼ 0.4–0.6.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…Reichard et al (2009) recently reported a connection between AGN activity and lopsidedness of their host galaxies. An outer loop and an arc with blue colours were observed in Seyfert 1.8 galaxy Mark 334 at a radius r ∼ 20–30 arcsec from the centre (Smirnova & Moiseev 2010). The blue colours suggest the existence of young stellar populations (∼0.5–1 Gyr) that are formed in the interaction process.…”
Section: Conclusion and Discussionmentioning
confidence: 99%